Nuclear Factor Erythroid 2-Related Factor 2 Intervenes the Release of Neutrophil Extracellular Traps during Lipopolysaccharide-Induced Acute Lung Injury in Mice - Junying Lu; Guilan Xiong; Hongxiang Li; Dong Zhang; Xiaohao Zhang (Mediators of Inflammation)
The pathogenesis of acute lung injury is complex. Studies have demonstrated the role of neutrophil extracellular traps (NETs) in the process of lipopolysaccharide (LPS)-induced acute lung injury (ALI). However, the underlying mechanism remains unclear. In this study, the regulation of Nrf2 in the formation of NETs, which was pathogenic in LPS-induced ALI, was identified by analyzing the levels of Cit-H3, lung function, lung tissue pathology, lung wet/dry ratio, the inflammatory cells, cytokines and proteins in the bronchoalveolar lavage fluid (BALF) and in addition, the activity of lung myeloperoxidase (MPO) was also measured. Results showed that the levels of Cit-H3 measured by western blot in Nrf2-knockout (KO) mice were higher compared with the WT mice after LPS stimulation. To further investigate the NETs formation was pathogenic during LPS-induced ALI, the Nrf2-KO mice were treated with DNase I. Results showed that DNase I improved lung function and lung tissue pathology and significantly reduced lung wet/dry ratio and proteins in the BALF. Besides, DNase I also attenuated the infiltration of inflammatory cells and the cytokines (TNF-α, IL-1β) production in the BALF and the activity of lung MPO. Therefore, these results together indicate that Nrf2 may intervene in the release of NETs during LPS-induced ALI in mice.